Novel insights on the role of CD8+ T cells and cytotoxic responses during Helicobacter pylori infection - Kronsteiner, Barbara (Landes Bioscience, 2014)
Helicobacter pylori chronically persists in 50% of the human population and causes serious gastric and duodenal pathologies in 15% of infected people. Research on the immune response to the infection has mainly focused on the induction of CD4+ T cell responses. Human studies emphasize the potential clinical relevance of CD8+ cytotoxic T lymphocytes, however this cell type has barely been reported in studies employing mouse or gerbil models. Traditionally characterized as an extracellular bacterium, H. pylori has been identified inside epithelial and immune cells. Similarly to other intracellular bacteria, H. pylori infection of macrophages can alter autophagy and phagosome processing. A novel animal model of H. pylori infection demonstrates for the first time the induction of cytotoxic CD8+ T cell responses in pigs and localization of intracellular H. pylori within lymphoid aggregates. Here, we discuss novel mechanisms of host-H. pylori interactions that could lead to the induction of cytotoxic responses.